Selecting Cover Crop Mulches for Organic Rotational No‐Till Systems in Manitoba, Canada. (1st July 2014) - Halde, Caroline; Gulden, Robert H.; Entz, Martin H.
Abstract : In western Canada, limited research has been conducted on reduced‐tillage grain production systems managed organically. The objective was to select cover crop mulches for an organic rotational no‐till system in Manitoba. A 2‐yr field study (2010–2011, and repeated 2011–2012) was conducted in Carman, MB, Canada. In the cover crop year, 10 different combinations of cover crop species were seeded in the spring, in pure stand or in mixtures, and rolled using a roller‐crimper in mid‐summer, at the flowering stage. These rolled mulches were then left on the soil surface over the fall and winter. The following spring, spring wheat ( Triticum aestivum L.) was seeded directly into these mulches (no‐till). Mulches with hairy vetch ( Vicia villosa Roth) showed the most promising results. Cover crop treatments with vetch had the highest mulch biomass in September of the cover crop year (9.1–10.7 Mg ha −1 ), and in the following spring (6.0–7.6 Mg ha −1 ) and provided the best weed control. In late fall of the cover crop year, N content of mulches with vetch reached high levels (308 kg N ha −1 on average), and high amounts of N (93–164 kg N ha −1 ) were released from these mulches over winter. Organic spring wheat no‐till planted into mulches with vetch produced yields comparable to regional conventional average yields. Mulches with vetch used in an organic rotational no‐till system reduced the need for tillage for a period of 1.5 to 2 yr without affecting yields of organic spring wheat.